PENGARUH BUDAYA ORGANISASI, GAYA KEPEMIMPINAN, SISTEM INFORMASI AKUNTANSI DAN STANDAR AKUNTANSI PEMERINTAH TERHADAP KINERJA ORGANISASI PADA PEMERINTAH DAERAH KABUPATEN SUMBAWA - - Sadad; Endar Pituringsih; M Irwan (Master of Accounting Universitas Trunojoyo Madura, 2016)
This study was conducted to examine the influence of organizational culture , leadership style , accounting information systems and government accounting standards on organizational performance Sumbawa Regency government . Objects in this study are echelon II , III Echelon and Echelon IV. Respondents were asked to answer a list of questions in the questionnaire formDistribution of the questionnaire as many as 90 copies to all agencies , but which can be analyzed only 84 questionnaires.Processing and analysis of data using multiple linear regression method with SPSS version 18.0.Results based on test data analysis showed that the variables t Cultural organizations and government accounting standards significant positive effect on the performance of local government organizations Sumbawa.While the leadership style variable and accounting information systems showed no effect on organizational performance at local government district, Sumbawa. Based on the value of the F test showed that the variables of organizational culture , leadership style , accounting information systems and accounting standards of government influence simultaneously on the performance of local government organizations Sumbawa.